A new chaotic image encryption algorithm based on dynamic DNA coding and RNA computing - Cun, Qiqi; Tong, Xiaojun; Wang, Zhu; Zhang, Miao (The Visual computer, 2023)
In order to improve the complexity of the chaotic system and ensure the relevant security indicators of the cryptographic algorithm, a new chaotic image encryption algorithm based on dynamic DNA coding and RNA computing is proposed. In this paper, we first construct a four-dimensional hyperchaotic system with more complex dynamics and then use the plaintext-related keystream generated by the hyperchaotic system to dynamically DNA encode the plaintext image, then perform RNA coding conversion and amino acid substitution box generation, and finally use an improved replacement sequence generator to generate pseudo-random sequences for replacement operations to generate the final ciphertext image. Theoretical analysis and simulation results show that the proposed algorithm has excellent performance in security indicators such as key space, the number of pixels change rate, the number average changing intensity, entropy, clipping attack, noise attack, and chosen plaintext attack. Therefore, the algorithm has higher security.